Implementation of Lecturer's Professional Competency in Assessing Financial Performance - Agus Eko Sujianto (EDUTEC : Journal of Education And Technology, 2021)
This research is intended to implement the lecturer's professional competence, especially in assessing the performance of Puskesmas from the aspect of current ratio, efficiency ratio, and ROA. The research approach chosen is quantitative with descriptive research. The data collection technique uses documentation, namely financial reports published by Puskesmas "X" in 2016 and 2017. The results of the study explain that as a government institution managed using the BLUD mechanism, Puskesmas always pays attention to the management process for accounts as stipulated in public sector accounting that becomes an important part of assessing financial performance. Based on the current ratio, the ratio of total current assets and total current liabilities increased from 2016 to 2017 so that the performance of the Puskesmas was good. In the aspect of efficiency ratio, the comparison of expenditure realization and revenue realization of Puskesmas shows that puskesmas are efficient, especially in 2017. Puskesmas are also Quite Effective or Good Enough in generating ROA, so that in general this puskesmas works well, efficiently, and quite well in 2017.